Dynamical solitons and other solutions for nonlinear Biswas–Milovic equation with Kudryashov’s law by improved modified extended tanh-function method - Rabie, Wafaa B.; Ahmed, Hamdy M. (Optik (Stuttgart), 2021)
In this work, optical solitons of nonlinear Biswas–Milovic equation with Kudryashov’s law are obtained by using the improved modified extended tanh-function method. This method reveals several optical solitons including traveling wave solutions. The found solutions are identified with different forms including bright soliton solutions, dark soliton solutions, singular soliton solutions, bright–singular combo soliton solutions, periodic solutions, rational solutions, Jacobi elliptic solutions, Weierstrass elliptic doubly periodic solutions, exponential solutions. The constraint conditions for the existence of these solutions are also given. Finally, two-dimensional, three-dimensional and contour graphs of some solutions are introduced for knowing the physical interpretation.